2021
DOI: 10.21203/rs.3.rs-882601/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Level-1 Visual Perspective Taking Performance in People with High Narcissistic Traits

Abstract: Background: Lack of empathy is one of the main characteristics of narcissists. However, it is not clear whether there is a similar deficit in other facets of mentalizing, such as perspective-taking.Method: In this study, we measured the taking visual perspectives ascribed to different targets (e.g., first-person self, third-person self-avatar, and third-person stranger avatar). Our study focused on separate groups of individuals with high and low self-reported narcissistic traits. Results: Participants report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Given the counter-intuitive direction of the association, we conducted a second study which replicated that negative association on a larger sample. Further, a recent preprint study (Ebrahimian et al, 2021) reported a similar result with a similar visual perspectivetaking task: narcissists were better to judge from a 3 rd person perspective and were better when the third person character was tagged as another person (versus themselves). This set of findings strongly support the hypothesis that narcissists are actually not more egocentric but less egocentric.…”
Section: A Novel Measure Of Egocentrismmentioning
confidence: 60%
“…Given the counter-intuitive direction of the association, we conducted a second study which replicated that negative association on a larger sample. Further, a recent preprint study (Ebrahimian et al, 2021) reported a similar result with a similar visual perspectivetaking task: narcissists were better to judge from a 3 rd person perspective and were better when the third person character was tagged as another person (versus themselves). This set of findings strongly support the hypothesis that narcissists are actually not more egocentric but less egocentric.…”
Section: A Novel Measure Of Egocentrismmentioning
confidence: 60%